2016
DOI: 10.1002/mnfr.201600079
|View full text |Cite
|
Sign up to set email alerts
|

Gene promoter DNA methylation patterns have a limited role in orchestrating transcriptional changes in the fetal liver in response to maternal folate depletion during pregnancy

Abstract: ScopeEarly‐life exposures are critical in fetal programming and may influence function and health in later life. Adequate maternal folate consumption during pregnancy is essential for healthy fetal development and long‐term offspring health. The mechanisms underlying fetal programming are poorly understood, but are likely to involve gene regulation. Epigenetic marks, including DNA methylation, regulate gene expression and are modifiable by folate supply. We observed transcriptional changes in fetal liver in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 61 publications
5
26
0
Order By: Relevance
“…Whilst we observed simultaneous changes in gene expression and promoter DNA methylation in response to both nutritional exposures investigated, we found no significant overlap between gene lists for which expression and promoter methylation were altered in response to a given exposure. These data corroborate our previous findings in the fetal liver in response to maternal folate depletion [66], and data from other studies reporting non-synonymous changes in gene expression and promoter DNA methylation [69][70][71][72]. However, as previously explored [66], we used PGE analysis to find regions of the genome enriched for changes in gene expression and promoter DNA methylation in response to maternal low folate and high fat intake post-weaning to test the hypothesis that methylation status of a gene promoter may not influence the expression of that specific gene but could influence expression of a neighbouring gene(s), as has been demonstrated by others [73].…”
Section: Maternal Folate Depletion and Post-weaning High Fat Intake Asupporting
confidence: 93%
See 3 more Smart Citations
“…Whilst we observed simultaneous changes in gene expression and promoter DNA methylation in response to both nutritional exposures investigated, we found no significant overlap between gene lists for which expression and promoter methylation were altered in response to a given exposure. These data corroborate our previous findings in the fetal liver in response to maternal folate depletion [66], and data from other studies reporting non-synonymous changes in gene expression and promoter DNA methylation [69][70][71][72]. However, as previously explored [66], we used PGE analysis to find regions of the genome enriched for changes in gene expression and promoter DNA methylation in response to maternal low folate and high fat intake post-weaning to test the hypothesis that methylation status of a gene promoter may not influence the expression of that specific gene but could influence expression of a neighbouring gene(s), as has been demonstrated by others [73].…”
Section: Maternal Folate Depletion and Post-weaning High Fat Intake Asupporting
confidence: 93%
“…in response to maternal folate depletion, 1859 genes were differentially expressed and 201 gene promotors differentially methylated; in response to high fat intake from weaning, 1532 genes were differentially expressed and 324 gene promotors differentially methylated). We have previously reported that folate depletion during pregnancy evoked approximately three times more changes in expression than in DNA methylation (expression of 989 genes v. methylation of 333 gene promoters) in the fetal liver . Others have reported genome‐wide, but also relatively small, changes in DNA methylation in the liver of rat offspring from dams fed a high‐fat diet (45% of energy from fat) throughout gestation and lactation and to the offspring from weaning until 12 weeks of age .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…) but, at least for folate restriction, alterations in DNA methylation do not appear to correspond directly with changes in gene expression in the fetal liver (McKay et al . ).…”
Section: Nutrition and Epigenetics Across The Life Coursementioning
confidence: 97%